The Architecture Characterization of Braided River Reservoirs in the Presence of Horizontal Wells—An Application in a Tight Gas Reservoir in the North Ordos Basin, China - Qi Chen; Yuming Liu; Ze Feng; Jiagen Hou; Lei Bao; Zhuang Liang (Energies, 2023)
The study of the reservoir architecture in braided river systems has significant implications for the exploitation of remaining oil and gas reserves. However, due to the complexity of the braided river deposition process, the architecture patterns are diverse and intricate. Limited by the quality of seismic data and well network density, the characterization of underground reservoir architecture often entails considerable uncertainty. This paper investigates the architecture elements, stacking patterns, and significance of oil and gas development in the braided river deposition of the Jin 58 well area in the northern part of the Ordos Basin through typical field outcrop and core observations, and by making full use of horizontal well data. The study reveals that the Jin 58 well area is mainly characterized by four types of architecture units: braided channel, channel bar, overbank, and flood plain. Based on the data from horizontal and vertical wells, four identification criteria for single sand bodies are determined, and the vertical stacking and lateral juxtaposition styles of the architecture units, as well as the architecture patterns and internal features of the channel bar, are summarized. It is confirmed that composite sand bodies have better productivity. A three-dimensional architecture model of the braided river is established based on the results of architecture analysis. The accuracy of the architecture analysis is validated through numerical simulation, providing a basis for subsequent well deployment and other related activities.